Selected Cases From the Arkadi M. Rywlin International Pathology Slide Series: Granular Cell Nevus of Congenital Type. (July 2015) - De Pellegrin, Alessandro; Luzar, Bostjan; Suster, Saul; Falconieri, Giovanni
Abstract : A case of combined melanocytic nevus characterized by extensive granular cytoplasmic changes is described. Clinically, the lesion presented as an irregular, slightly asymmetric, and raised pigmented lesion of back with indistinct borders. Microscopically, a congenital pattern of distribution of melanocytes could be recognized growing along follicular and adnexal units. Melanocytes were arranged in sheets of epithelioid cells with abundant granular cytoplasm. A minor component featuring conventional dermal melanocytes was also present. Mitotic figures were not recognized. Immunohistochemistry was positive for Melan A and S100 protein in both conventional melanocytes and granular cells. In addition, the granular cells were also strongly positive for HMB45 and NKI-C3. The proliferative marker Ki67/MIB1 was nonreactive. Ultrastructural examination showed large cells with round to oval nuclei and numerous scattered cytoplasmic granules showing features consistent with lysosomes or autophagosomes. No premelanosomes, glycogen, lipid, or other distinctive organelles could be identified. Clinical follow-up at 2 years was uneventful. This unusual lesion may represent a peculiar dermal melanocytic proliferation in which the abundant granular cytoplasm is most likely due to degeneration of melanosomes induced by autophagocytic activity. The striking cytoplasmic granularity observed in this lesion may lead to confusion with other conditions, thus warranting adding granular cell nevus to the phenotypic spectrum of benign melanocytic proliferations.